PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Gunawan, Alvina; HARJANTO, KARINA (Universitas Multimedia Nusantara, 2019)
The objective of this research is to obtain empirical evidence about the effect of profitability, leverage, company's size, company's growth and structure ownership towards dividend policy. The sample in this research is selected by using purposive sampling method. Data used in this research are secondary data. Data used in this research is analyzed by using multiple regression method. There are 10 manufacture firms selected as sample which simultaneously for the year 2013-2016 have been registered as manufacture sector in the Bursa Efek Indonesia (BEI). The results of this research show that (1) profitability has significant effect to dividend policy, (2) leverage doesn't have significant effect to dividend policy, (3) company's size has significant effect to dividend policy, (4) company's growth doesn't have significant effect to dividend policy, (5) structure ownership doesn't have significant effect to dividend policy.